A comprehensive insight into the effects of microwave-H2O2 pretreatment on concentrated sewage sludge anaerobic digestion based on semi-continuous operation. (May 2018) - Liu, Jibao; Yang, Min; Zhang, Junya; Zheng, Jiaxi; Xu, Hui; Wang, Yawei; Wei, Yuansong
Graphical abstract: Highlights: Methane production was improved by 19.89% due to MW-H2 O2 pretreatment. Enhanced performance was derived from various aspects except for SCOD release. Pretreatment increased the relative abundance of some functional microbia. Shifted methanogens community is the key for high efficiency and stability. Reduced sludge viscosity was in favor of improving mass transfer efficiency. Abstract: This study gave a comprehensive insight into the effects of microwave-H2 O2 pretreatment on concentrated sludge anaerobic digestion (AD). Results showed that mixture of activated sludge and pretreated sludge at mass ratio of 1:1 was efficient for enhancing AD, methane production was increased from 215.51 mL/g VSadded to 258.38 mL/g VSadded . Pretreatment resulted in the change of sludge properties, such as solubilization of organic matters, decrease of viscosity. For concentrated sludge AD, the "pH buffer system" ensured the "inhibitory steady state" during start-up period, and significant archaeal community shift from Methanosaeta to Methanosarcina ensured the true steady-state operation. Pretreatment further increased the relative abundance of functional microbia such as Bacteroidales, Clostridiales and Methanosarcina, and resulted in the decrease of viscosity of digested sludge in reactors. Based on the CFD simulation, the flow velocity became greater than the control. These comprehensive effects might contribute to enhanced efficiency of concentrated sludge AD.